Young adults’ perceptions of the effectiveness of HIV/AIDS awareness campaigns as an instrument for reducing risk-bearing sexual behaviour - nomhle@tuks.co.za (University of Pretoria, 2013)
Dissertation (MA (Research Psychology))--University of Pretoria, 2011.